Connectivism Practice in English Language Teaching (ELT): Teachers' Perception on Benefits and Challenges - Azizah, Rizki; Shinta, Aninda; Endang Fauziati; Koesoemo Ratih (Journal of International Multidisciplinary Research, 2024)
Connectivism provides abundant enchanting experiences in ELT context due to the benefits that it offers. However, as the practice requires technology integration, physical, and psychological readiness, teachers discover challenges upon the implementation. This study aims at investigating the benefits and challenges of the practice in ELT context. Through content analysis qualitative study, the study attains the targeted exploration. 5 experienced English teachers are selected to conduct semi-structured interviews. The data were analyzed and reviewed by the researchers and experts for affording the valid results. The results provide valuable insights towards the issues that are raised. This study sheds a light on the essence of digital environment in ELT which assists the feasible various sources of learning to be attained. Findings revealed that Connectivism can definitely foster learners’ language skills, such as speaking, listening, and pronunciation through the various digital platforms that are provided. Interestingly, connectivism is advantageous for strengthening learners' 21st century skills, namely critical thinking, collaboration, communication skills, and creativity in learning English. On the other hand, the challenges encountered by teachers in integrating connectivism are 1) inadequate facilities and infrastructure, 2) lack of training and development in educator resources, and 3) low internet network access or the bandwidth.